2021
DOI: 10.1002/aoc.6137
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization and evaluation of novel ferrocenylmethylamine derivatives as cytotoxic agents

Abstract: The present report describes a new series of amide functionalized 2 0-and 3 0-aminomethylferrocene derived from ferrocenylmethylamine. The compounds 1a-5a and 1b-5b were characterized by microanalysis, 1 H, 13 C NMR, UV-visible, fluorescence, FTIR, thermogravimetric and crystallographic techniques. The X-ray analysis demonstrated the ability of these molecules to form various intermolecular hydrogen bonding interactions, as verified by Hirshfeld surface analysis. All the compounds were evaluated against MCF 7,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Similarly, strongly cytotoxic ferrocenyl amino phosphines with IC 50 =6.9 μg mL −1 against HT1376 cells, or IC 50 <5 μg mL −1 against Hep3B cells, have been reported [7g,27] . In previous studies, [7e,i] simple ferrocenyl amines with activities in vitro against tumour cells comparable to those presented in Table 1 have been displayed. In some other contributions, however, ferrocenyl amines have been described as inactive or having very little antitumour activity [7a,28,29] .…”
Section: Resultsmentioning
confidence: 69%
“…Similarly, strongly cytotoxic ferrocenyl amino phosphines with IC 50 =6.9 μg mL −1 against HT1376 cells, or IC 50 <5 μg mL −1 against Hep3B cells, have been reported [7g,27] . In previous studies, [7e,i] simple ferrocenyl amines with activities in vitro against tumour cells comparable to those presented in Table 1 have been displayed. In some other contributions, however, ferrocenyl amines have been described as inactive or having very little antitumour activity [7a,28,29] .…”
Section: Resultsmentioning
confidence: 69%
“…Density functional theory (DFT) is often used in the simulation and prediction of metal complexes, and studies have shown that results of DFT calculations are highly consistent with experimental results. [26][27][28][29][30] Indeed, theoretical DFT calculations may be suitable replacements for conventional experimental research. [31][32][33] Although DFT has been used to analyze heme and heme derivatives.…”
Section: Introductionmentioning
confidence: 99%